The role of cooperative relations in exercising Common specialties and settling disputes between the two levels of government in the federal state (Analytical study) - Abdulrahman, Shalaw Sabah; Majeed, Suz Hamid (Journal of Legal and Political Studies, 2025)
There are two levels of government in the federal state, the federal level and the level of federal units, the federal constitution defines the powers of each level of government, and there is also a supreme constitutional judiciary to resolve legal disputes that occur between federal units or between units and the federal government. However, the nature of the federal system requires that there be cooperative relations between the units with each other, and between the federal units and the federal authorities with the aim of exercising the joint powers stipulated in the federal constitution and agreeing on projects and implementing them, in addition to settling disputes that occur between them due to the exercise of these powers. Cooperative relations take different and varied forms between the levels of government, so that these relations may be informal, and they may be official. Keywords: Federalism, Cooperative Federalism, Federal Units, Shared Competencies.
Keywords: Federalism; Cooperative Federalism; Federal Units; Shared Competencies